Navigating Filiation/Affiliation: Re-visioning Diasporic Experience in Yasmine Gooneratne’s A Change of Skies - Singh, Nidhi (Asiatic: IIUM Journal of English Language and Literature, 2017)
Problematics of filiation and affiliation underscore the Janus-faced diasporic sensibility of Yasmine Gooneratne, equipoised between the esoteric pull of the ancestral allegiances and the allure of a promising future in the new land. Gooneratne’s novel A Change of Skies (1991) explores the trajectory of journey and consequent experiences of two generations of diaspora. There is a constant negotiation of the emotional and the social, the cultural and the political. Exposed to European influence during colonial era, independent South Asian nations have been progressively impacted by forces of modernisation and Globalisation. Technological advancement revolutionised communication and opened the floodgates of cross-border movement owing to the opportunities generated. The floating population of transnationals constantly navigate the porous boundaries of filiation and affiliation. The body of literature produced by the diaspora is haunted by these contradictory allegiances, as is evident in the novels of Gooneratne. The paper attempts to interrogate Yasmine Gooneratne’s re-visioning of immigrant experiences from the vantage point of diasporic consciousness shaped by colonial/postcolonial island nation Sri Lanka and the settler colony of island continent Australia.